Tanggung Jawab Sosial Dan Modal Intelektual Terhadap Kinerja Keuangan Perusahaan Manufaktur Konsumsi - Yeremia Wijaya, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to determine the effect of Corporate Social Responsibility and Intellectual Capital on Financial Performance in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2012-2018 period. Sampling uses a purposive sampling method that obtains 50 samples of manufacturing companies. The data used are secondary data in the form of financial information from financial statements. The data processing of this research uses the IBM SPSS STATISTICS 25 and SmartPLS 3.3.2 programs. The F test results show that corporate social responsibility and intellectual capital together have a significant influence on financial performance. t test results indicate corporate social responsibility has a positive and significant impact on financial performance. Meanwhile, intellectual capital together has a negative and significant effect on financial performance.